Coming back home: the reconstruction of the identities of the homecomers (Revista Tempo e Argumento, 2019)
AbstractThis article discusses the comings and goings of Brazilian migrants in the early 21st century. Returning is a constituent stage of the migration project. Many men and women, when setting out to America, claimed their intent to come back when completing their migration project, which is usually translated as acquiring enough resources to purchase a house, a vehicle, and to start a business. This article discusses how men and women go through the experience of returning to the homeland to analyze how they reconstruct the path home and which effects of travel appear in the identity configurations, as well as in familial and gender relations. “It’s easier to leave than to come back,” migrants say. Thus we intend to demonstrate that returning is more complex, and that, in several cases, migrants live between two places, forming a transnational identity. Keywords: Transnationalism. Return. Memory